Os efeitos do crédito sobre o crescimento econômico dos municípios do Espírito Santo: uma análise econométrica espacial com dados em painel - Fraga Junior, Jandir (2022)
This study investigates the effects of credit volume on economic growth (measured by GDP per capita) of municipalities in the state of Espírito Santo, considering the period from 2006 to 2018, using spatial econometrics for panel data, which allows verify spatial spillover effects. In addition to using the supply of credit as a treatment variable, adopt the variable number of branches (also a treatment variable), and control over the stock of formal employment by municipality and the number of enrollments. First, we analyze the characteristics of the space-time distribution of the volume of municipal credit, the number of banking institutions and economic growth. Then, the global Moran I statistic is applied to detect the presence of spatial autocorrelation. With regard to econometric estimates, all estimated spatial models revealed inspired effects, with the Durbin spatial model (SDM) presenting the best fit when using the Akaike information resource (AIC). The main results showed that the variables: credit supply and number of branches, without spatial lag, were significantly and positively correlated with the economic growth of the municipalities of Espírito Santo. In addition, there were spatial spillover effects of the variables: credit supply, number of branches and GDP per capita on the economic growth of municipalities. It is noteworthy that the variables number of branches and GDP per capita had a positive spatial relationship with economic growth, while the spatially lagged credit offer had a negative relationship. Thus, it is clear that public policies related to the supply of credit and the number of bank branches are important and can lead to good medical outcomes in terms of economic growth in the municipalities of Espírito Santo.